Food Availability in the Heartland: Exploring the Effects of Neighborhood Racial and Income Composition1. (24th February 2015) - Miller, Michael; Middendorf, Gerad; Wood, Spencer D.
Abstract This article examines the relationships between neighborhood racial and income composition and healthy food availability. We explore the extent to which physical and social isolation affects healthy food availability for groups marginalized by race and class in a context largely missing from the literature. We use census tract data and five‐year estimates from the American Community Survey to produce maps illustrating the patterns of race and income composition in Topeka, Kansas. Included in these maps are data points illustrating the distribution of stores offering healthy foods. We find that, as in the large metro areas analyzed thus far, the distribution of healthy food stores in Topeka is similarly patterned. Blacker (and poorer) neighborhoods tend to have the lowest levels of healthy food availability. We conclude with a discussion of the relevance of this work to the knowledge base regarding food environments and health in the United States.